Second Language Pronunciation Assessment Interdisciplinary Perspectives - Isaacs, Talia; Trofimovich, Pavel (Second Language Acquisition, 2017)
This book is open access under a CC BY licence. It spans the areas of assessment, second language acquisition (SLA) and pronunciation and examines topical issues and challenges that relate to formal and informal assessments of second language (L2) speech in classroom, research and real-world contexts. It showcases insights from assessing other skills (e.g. listening and writing) and highlights perspectives from research in speech sciences, SLA, psycholinguistics and sociolinguistics, including lingua franca communication, with concrete implications for pronunciation assessment. This collection will help to establish commonalities across research areas and facilitate greater consensus about key issues, terminology and best practice in L2 pronunciation research and assessment. Due to its interdisciplinary nature, this book will appeal to a mixed audience of researchers, graduate students, teacher-educators and exam board staff with varying levels of expertise in pronunciation and assessment and wide-ranging interests in applied linguistics.